Control of oxidation behavior in high vacuum transmission electron microscopy - Kwon, Yena; An, Byeong Seon; Moon, Ji Yun; Lee, Jae Hyun; Yoo, Hyunjae; Whang, Dongmok; Yang, Cheol Woong (Materials Characterization, 2021)
Transmission electron microscopy (TEM) is a critical tool evaluating nanoscale phenomena that occur in nanomaterials. Although TEM is a high-vacuum instrument, due to the presence of molecules remaining under the equilibrium gas partial pressure, unintended reactions can be thermodynamically driven by various factors during TEM observation. In particular, highly reactive gas molecules, such as oxygen, can react with the specimen and reduce the reliability of the analysis result. In this work, an oxidation reaction caused by the electron beam irradiation and heating in a microscope was studied using pristine copper nanowires (Cu NWs), with a high oxygen affinity. Real-time imaging revealed that the beam irradiation and heat led to a transition of Cu to Cu oxides due to residual oxygen in the microscope. This study also presents a method (i.e., graphene encapsulation) for preventing the unintended oxidation reaction of a TEM specimen. The proposed method is not only effective in inhibiting oxidation of Cu NWs induced by electron beam irradiation and heating, but also effective in preserving specimens for prolonged periods.
Keywords: Copper nanowires; Electron beam irradiation; Gas partial pressure; High oxygen affinity; Nanoscale phenomenon; Oxidation behaviors; Oxidation reactions; TEM observations; Copper nanowire; Electron beam irradiation; Graphene encapsulation; High-vacuum transmission electron microscopy; In situ heating; Oxidation reaction